INHIBITORY EFFECT OF AN ENDOGENOUS FACTOR (S) ON THE PROLIFERATION OF MOUSE FIBROSARCOMA CELL LINE Gc-4 PF MAINTAINED IN PROTEIN-FREE MEDIUM - SHIBA, SHUNSUKE (The KITAKANTO Medical Journal, 1995)
Murine fibrosarcoma cell line Gc-4 PF grows exponentially in protein-free medium. The effect of conditioned medium of this tumor cell line on its growth was examined. The dye exclusion test and MTT assay showed that its growth was inhibited by addition of the crude fraction concentrated from the conditioned medium of this tumor cell line. The more cells plated initially, the earlier the inhibitory effect on growth was detected, suggesting that these cells produced a putative inhibitory factor (s) and that it acted on the cells in an autocrine fashion. Flow cytometric analysis using Hoechst 33342 dye revealed that the conditioned medium concentrate increased the number of small cells staining blue with strong fluorescence. However, neither cleavage of DNA into internucleosomal fragments nor its cleavage into high molecular weight fragments, which could be detected by pulse field gel electrophoresis, was augmented by addition of the conditioned medium concentrate. Flow cytometry showed no marked induction of cell cycle arrest in a specific phase of the cell cycle by the conditioned medium concentrate, although 10% decrease in cells in the S phase and 10% increase in the G2/ M phase were detected. These results suggest that Gc-4 PF cells that can grow in protein-free culture medium secrete a factor (s) which induces their own death and that the process of cell death might be apoptosis, which is independent of DNA fragmentation.